Dampak Penerbitan Surat Utang Negara (SUN) dan Surat Berharga Syariah Negara (SBSN) Pada Pertumbuhan Ekonomi Indonesia Era Pandemi Covid-19: Tinjauan Ekonomi Islam - Khavid Normasyhuri; Budimansyah Budimansyah; Eko Triyadi (ITB AAS INDONESIA Surakarta, 2022)
Covid-19 has a very wide impact throughout the world and even Indonesia and has caused an economic crisis and caused Indonesia's economic growth to experience shocks. In order to create an increase in Indonesia's economic growth in the era of the Covid-19 pandemic, the government, as the leading economic sector, utilizes several sources of financing, some of which are Government Securities (SUN) and State Sharia Securities (SBSN). But on the other hand, this can actually lead to a debt burden and debt interest that will burden the government budget and ultimately hamper Indonesia's economic growth during the Covid-19 pandemic era. This research includes quantitative research with associative approach. The data used uses secondary data from the official website of Bank Indonesia (BI) which is then tested using the statistical tool Eviews Version 9. The study was conducted in Indonesia with the aim of seeing the impact of the issuance of Government Securities (SUN) and State Sharia Securities (SBSN). On Indonesia's Economic Growth in the Era of the Covid-19 Pandemic In An Islamic Economic Review. The results showed that the issuance of Government Securities (SUN) had a negative and insignificant effect on Indonesia's Economic Growth in the era of the covid-19 pandemic. In the view of Islamic economics, Government Securities (SUN) violate the principle of la tazhlimuna wa la Tuzhlamun, namely oppressing and being wronged. This includes because the State abuses itself and oppresses investors because the returns used in Government Securities (SUN) use interest that is usurious and the absence of basic assets. Then the issuance of State Sharia Securities (SBSN) has a positive and significant impact on Indonesia's Economic Growth in the era of the Covid-19 pandemic. In a review of Islamic economics, State Sharia Securities (SBSN) stand on the basis of cooperation (musharaka) in funding a development or it can also be said as an investment business.